Lexical Paradigms of Satirical Fables of the Polish Enlightenment (Linguostylistic Studies, 2020)
This article investigates the language of fables of the 18th-century Polish writer F. D. Kniaźnin. Due to its high capacity of influencing collective consciousness, and its propagandistic character, Polish literature of that period, along with philosophy and education, became the main source for spreading the ideas of Enlightenment. This was true for other parts of Europe at the time, as well. Short rhymed fables written on burning issues played a special role in this process. In modern lexicology, groups of structurally and systemically related words are called semantic fields, lexico-grammatical groups, thematic groups, associative fields, lexical microsystems, paradigmatic rows, groups of concepts. In terms of stylistics of poetry, these acquire different dimensions as they determine the style and the linguistic image of the world of an author, as well as the predominant linguistic taste of the epoch in general. Functional analysis of a writer’s lexicon, particularly with quantitative parameters in question, enables the identification of microsystems of lexemes of the highest frequency, which, in turn, form a grid of dominants of a text. A review into fables of F. D. Kniaźnin  reveals the following paradigms of dominants of their lexical layer: 1) collective names of groups of people (organized as a lexico-semantic group); 2) names of persons according to their place of  residence, social background, occupation or title (lexico-semantic group); 3) concepts of philosophy (lexico-semantic group); 4) types of conscious human activity (lexico-thematic group), 5) abstract notions for positive and negative phenomena of social and human nature (lexico-thematic group); 6) notions from fauna (lexico-semantic group). Such lexical structure fully discloses the subject-matter of fables, facilitates the comprehension of an author’s intent, and corresponds to general tendencies of development of Polish language and literature of the Age of Enlightenment.
Keywords: lexical paradigm,; fable,; idiostyle,; F. D. Kniaźnin,; Enlightenment.